Development of a Quizizz-Based Assessment Project-Based Learning Model to Enhance Elementary School Students' Adversity Quotient - Adinda Nurmaulinda; Irdalisa Irdalisa; Ishaq Nuriadin (AL-ISHLAH: Jurnal Pendidikan, 2025)
Developing students' Adversity Quotient (AQ)—the ability to persevere through challenges—is crucial for 21st-century learning. Yet, few studies explore how digital assessment tools like Quizizz can be integrated within Project-Based Learning (PjBL) to enhance AQ, particularly in elementary education. This study employed a Research and Development (RD) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). A Quizizz-based assessment-integrated PjBL model was designed and validated by material, media, and language experts. Data were collected through tests, observations, questionnaires, and expert validation sheets. Quantitative data were analyzed using descriptive statistics, paired-sample t-tests, and N-Gain scores, while qualitative data were analyzed via content analysis. The model demonstrated high validity across all expert evaluations. Students reported strong positive responses in terms of practicality, engagement, and user-friendliness (mean score: 91.01%). The model was effective in improving AQ, as shown by a significant increase in post-test scores (M = 109.81) compared to pre-test scores (M = 86.25; p 0.001) with an average N-Gain of 0.57 (medium category). Notably, the proportion of students categorized as Climbers increased from 12.5% to 93.75%. The integration of Quizizz into a structured PjBL model fosters both cognitive understanding and non-cognitive resilience. This model proves effective in cultivating AQ by leveraging gamified assessment features that support persistence, motivation, and reflective learning. Future applications should consider digital readiness and contextual adaptation to maximize impact.